The global importance of ticks - JONGEJAN, F.; UILENBERG, G. (Parasitology, 2004)
Ticks and tick-borne diseases affect animal and human health worldwide and are the cause of significant economic losses. Approximately 10% of the currently known 867 tick species act as vectors of a broad range of pathogens of domestic animals and humans and are also responsible for damage directly due to their feeding behaviour. The most important tick species and the effects they cause are listed. The impact on the global economy is considered to be high and although some estimates are given, there is a lack of reliable data. The impact of ticks and tick-borne diseases on animal production and public health and their control are discussed.